The Relationship Between Transformational Leadership and Followers’ Perceptions of Fairness - Bacha, Eliane; Walker, Sandra (2013)
Of recent time, there has been a concern about ethical leadership and ethics in business. Research on leadership did not pay a lot of attention to fairness and many authors have studied the relationship between leader fairness and factors such as outcome satisfaction and trust in leader for instance. For the moment, there is no study that focused on the direct relationship between transformational leadership and fairness. That’s why; in this paper our aim is to study the relationship between transformational leadership and the employees’ perceptions of fairness, mainly the three types of fairness which are distributive, procedural, and interactional in French firms. A questionnaire survey was sent to employees working in the industry and service sectors. A sample of 100 respondents was collected. We found a partial relationship between employees’ perceptions of fairness and transformational leadership. More specifically, we found that procedural and interactional fairness are strongly associated with transformational leadership.
Keywords: Transformational Leadership; Procedural Fairness; Perceptions of fairness; Interactional fairness; Distributive fairness; France; Fairness